Overall review on annalytical method development and validation of Nilotinib Hydrochloride - Nuli, Mohana Vamsi; Rekulapally, Vijay Kumar (International Journal of Indigenous Herbs and Drugs, 2023)
In this review, the article determines the different analytical methods for the quantitative establishment of Nilotinib by using HPLC, HPLC-MS, HPLC-UV, and LC-MS/MS. Pharmaceutical analytical method development of Nilotinib requires valid analytical procedures for quantitative and qualitative analysis in Pharmaceuticals dosage formulations and human serum. This assessment explains that the superiority of the HPLC/LC-MS methods reviewed is based on the quantitative analysis of drugs in formulations, (API), and biological fluids such as serum and plasma.